Feminist History in Canada: New Essays on Women, Gender, Work, and Nation - Janoviček, Nancy; Carstairs, Catherine (UBC Press, 2013)
In the late 1970s, feminist historians urged us to “rethink” Canada by placing women’s perspectives and experiences at the centre of historical analysis. Forty years later, feminism continues to inform history writing in Canada and has inspired historians to look beyond the nation and adopt a more global perspective. This exciting new volume of original essays opens with a discussion of the debates, themes, and methodological approaches that have preoccupied women’s and gender historians across Canada over the past twenty years. The chapters that follow showcase the work of new and established scholars who draw on the insights of critical race theory, postcolonial theory, and transnational history to re-examine familiar topics such as biography and oral history, paid and unpaid work, marriage and family, and women’s political action. Whether they focus on the marriage of Governor James Douglas and his Metis wife, Amelia; representations of saleswomen in department store catalogues; or the careers of professional women such as international child activist Charlotte Whitton and Quebec social work professors at Laval University, the contributors demonstrate the continued relevance – and growth – of history informed by feminist perspectives, and they open a much-needed dialogue between francophone and anglophone historians in Canada.– Publisher's description
Available to readers with print disabilities at Internet Archive: https://archive.org/details/feministhistoryi0000unse OCLC: 854497794
Keywords: Aufsatzsammlung; Biographies; Canada; Feminism; Feminism Canada History; Feminismus; Femmes Canada Biographies; Femmes Canada Conditions sociales; Femmes Canada Histoire; Frau; Frauenbewegung; Féminisme Canada Histoire; Geschlechterrolle; History; Kanada; Women; Women Canada Biography; Women Canada History; Women Canada Social conditions; Women Social conditions